Identifying and Assessing Health and Safety Program Implementation Barriers in the Construction Industry: A Case of Saudi Arabia - Ali Al-Otaibi; Ahmed Farouk Kineber (Applied Sciences)
A significant issue in the construction sector is poor safety performance. Construction sites are hazardous and prone to crashes, with several risks that can lead to accidents, injuries, or even the deaths of site workers or passing road users. Numerous studies have addressed this topic but there aren’t many studies in Saudi Arabia that are comparable. The purpose of this research is to determine which obstacles are standing in the way of the construction industry’s adoption of health and Safety Program. Starting with literature research, obstacles to the implementation of safety initiatives are noted. An analysis method known as the Partial Least Square Structural Equation Model (PLS-SEM) was utilized to look into additional barriers. It is recommended that a national governance structure be established in order to overcome these barriers and improve safety performance in the construction industry. Decision-makers would move decisively to establish and enhance safety practices in light of the proposed model’s outcomes. By identifying, assessing, and reducing the primary obstacles to safety program implementation, the study’s findings help Saudi Arabia improve safety practices for building projects.